2019
DOI: 10.1371/journal.pone.0215222
|View full text |Cite
|
Sign up to set email alerts
|

Unusual prevalence of high-risk genotypes of human papillomavirus in a group of women with neoplastic lesions and cervical cancer from Central Mexico

Abstract: Human papillomavirus has been identified as a main etiological agent in the development of cervical cancer. HPV 16 and 18 have been reported the most widely prevalent genotypes worldwide. We conducted a study analyzing the prevalence of high and low risk human papillomavirus viral types in the Mexican state of Aguascalientes and neighboring cities in the states of Jalisco and Zacatecas in central Mexico. Specific viral genotype was determined by a PCR and hybridization-based detection test. The presence of 37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…The prevalence of HPV51 was thus three times higher than that of HPV16 and seven times higher than that of HPV33. It is consistent with the results of recent studies, which have also found a high prevalence of HPV51 in Mexico ( Gallegos-Bolaños et al 2017 ; Jácome-Galarza et al 2017 ; Campos et al 2019 ) and other countries such as Turkey ( Gultekin et al 2018 ), Greece ( Argyri et al 2018 ), Italy ( Lillo et al 2001 ), Tanzania ( Mayaud et al 2001 ), Kenya ( Ferré et al 2019 ; Omire et al 2020 ) and Canada ( de Pokomandy et al 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of HPV51 was thus three times higher than that of HPV16 and seven times higher than that of HPV33. It is consistent with the results of recent studies, which have also found a high prevalence of HPV51 in Mexico ( Gallegos-Bolaños et al 2017 ; Jácome-Galarza et al 2017 ; Campos et al 2019 ) and other countries such as Turkey ( Gultekin et al 2018 ), Greece ( Argyri et al 2018 ), Italy ( Lillo et al 2001 ), Tanzania ( Mayaud et al 2001 ), Kenya ( Ferré et al 2019 ; Omire et al 2020 ) and Canada ( de Pokomandy et al 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…The polymorphisms of the most prevalent genotype were identified. In some areas of Mexico, HPV51 predominates over other genotypes ( Gallegos-Bolaños et al 2017 ; Jácome-Galarza et al 2017 ; Campos et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, growing evidence has highlighted that "uncommon" HPV types have higher incidence than HPV16 or 18. A recent work reported that HPV51 has a higher frequency than HPV16 in cervical cancer (49.5% versus 33.6%, respectively) in the states of Aguascalientes and Zacatecas [14]. In the southeastern state of Yucatan, HPV58 frequency was higher than HPV16 (28.5% versus 25.7%, respectively) [15].…”
Section: Discussionmentioning
confidence: 96%
“…Studies conducted in the Mexican population have shown differences in the prevalence of viral genotypes depending on the geographical area. For example, a study conducted in the states of Aguascalientes, Jalisco, and Zacatecas found that HPV 51 and 16 were the most prevalent genotypes [30]. A study based on the population in the state of Tlaxcala found that HPV types 16 and 18 had the highest prevalence [31].…”
Section: Discussionmentioning
confidence: 99%